Implementasi Manajemen Mutu Terpadu dalam Mewujudkan Sekolah Unggul di MAN 6 Jati Agung Kabupaten Lampung Selatan - Siti Nur Azizah; An An Andari; Cipto Handoko (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
This study aims to examine in depth how the implementation of Integrated Quality Management (IQM) is carried out as a collective and contextual process in realizing an excellent school at MAN 6 Jati Agung, South Lampung Regency. This study used a qualitative approach with a case study design to examine the implementation of IQM as a collective process at MAN 6 Jati Agung, South Lampung Regency. Subjects were purposively selected, including the principal, teachers, education staff, and related parties. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed interactively through reduction, presentation, and drawing conclusions. Data validity was maintained through triangulation of sources and methods. This study yielded an in-depth understanding of the collective practice of IQM and its contribution to the development of an adaptive and sustainable excellent school. The study concluded that the implementation of IQM at MAN 6 Jati Agung was holistic and contextual, emphasizing the collective involvement of all school members, continuous improvement practices, and participatory communication in decision-making. Responsibility for quality is clearly shared among the principal, teachers, education staff, and unit leaders, while a culture of quality develops through reflection, regular evaluation, and program adjustments to meet student needs. Participatory communication builds a sense of ownership, collective responsibility, and trust. This implementation creates an adaptive and sustainable educational management model that supports the overall achievement of excellent schools.